2000
DOI: 10.5694/j.1326-5377.2000.tb139363.x
|View full text |Cite
|
Sign up to set email alerts
|

A revolution in rural and remote Australia: bringing health education to the bush

Abstract: A network of academic health units in rural areas may help solve the problems of rural health

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In several overseas countries, medical schools have been established in rural regions and it has been shown that graduates from these schools are more likely to remain in rural medical practice 13,14 . Australia is following this trend and rural medical schools are in varying stages of development around the nation 15 …”
Section: Discussionmentioning
confidence: 99%
“…In several overseas countries, medical schools have been established in rural regions and it has been shown that graduates from these schools are more likely to remain in rural medical practice 13,14 . Australia is following this trend and rural medical schools are in varying stages of development around the nation 15 …”
Section: Discussionmentioning
confidence: 99%
“…There is a recent parallel. In an initiative designed to improve health in rural Australia, the Federal Government announced in 1996 the creation of seven University Departments of Rural Health, with most receiving core Commonwealth funding of A$1.5 million annually for an initial 5 years 3 . One or more new Australian Institutes of Trauma Research, similarly funded, could be expected to contribute substantially to injury reduction in the years to come.…”
Section: Discussionmentioning
confidence: 99%
“…Nowhere is this problem more acute than in non‐metropolitan Australia, where many rural and remote communities suffer from inadequate access to appropriate and sustainable quality medical care (Humphreys and Dixon, 2004). Despite more than a decade of innovative rural workforce recruitment and retention policies and programmes (Holub and Williams, 1996; Humphreys et al ., 2000; Lawson et al ., 2000), the difficulty of attracting medical practitioners, particularly domestic medical graduates, to take up rural or remote practice continues for many regions.…”
Section: Introductionmentioning
confidence: 99%